Pendampingan Majelis Pembina (MABIN) TPQ Annahdliyah Kota Metro dalam Beraktualisasi dan Berkontribusi Terhadap Pendidikan di Pemerintahan Kota Metro Lampung - Syaifullah, Muhammad; Izzah, Nailul; Fidani, Riki (Educivilia: Jurnal Pengabdian pada Masyarakat, 2022)
The Board of Trustees (MABIN) of the Al-Qur’an An-Nahdliyyah Education Park in Metro City was formed and ratified under the auspices of the Branch Management of the Ma’arif NU Educational Institution in Metro City which aims to strengthen capacity and reinforce identity, namely strengthening the capacity of TPQ under the auspices of MABIN TPQ Annahdliyah and confirming the identity that the use of the Annahdliyah method in TPQ is truly the hallmark of TPQ NU. Based on the appreciative findings through various work programs that have been carried out by the management of MABIN TPQ Annahdliyah Metro city and the discovery of problems in structural management and filling in the TPQ Emis data, there is an opportunity to provide assistance to the Management of the Board of Trustees (MABIN) Al-Qur’an An Education Park. - Nahdliyyah Metro City. With the intention that all TPQ units can carry out TPQ structural management properly and can fill in TPQ Emis data. The assistance provided to the management of MABIN TPQ Annahdliyah used the ABCD approach. Assistance in this approach prioritizes the utilization of the potential and assets that the community already has. In this approach, the main capital of the community in achieving change is the ability or potential. The results of the mentoring show that the TPQ-TPQ continue to improve the structural management of their respective TPQs, so that the results of these improvements can complement the data needed in the TPQ Emis data.